2022
DOI: 10.1002/aenm.202202207
|View full text |Cite
|
Sign up to set email alerts
|

Composition‐Conditioning Agent for Doped Spiro‐OMeTAD to Realize Highly Efficient and Stable Perovskite Solar Cells

Abstract: The doped Spiro‐OMeTAD hole transport layer (HTL) formed using the lithium bis(trifluoromethane) sulfonimide salt and 4‐tert‐butylpyridine with phenethylammonium iodide surface treatment on a perovskite film has continuously dominated the record power conversion efficiencies (PCEs) of perovskite solar cells (pero‐SCs). However, unstable HTL compositions and iodide salts can cause severe device degradation. In this study, an HTL composition‐conditioning agent (CCA), Spiro‐BD‐2OEG, is designed, which contains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 64 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…To determine the mechanism underlying the observed variations in V oc improvement, transient photovoltage (TPV) measurements were conducted (Figure 4d). The TPV curves are fitted with a biexponential decay function, [47] and the fitting results reveal that the charge recombination lifetime of the flexible Pero-I pero-SCs is longer (6.78 µs) than those of the Pero-Nbased (4.21 µs) and Pero-C-based (3.04 µs) devices. This lifetime observation suggests that the 1D/3D perovskite heterostructure efficiently suppresses the charge recombination processes.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the mechanism underlying the observed variations in V oc improvement, transient photovoltage (TPV) measurements were conducted (Figure 4d). The TPV curves are fitted with a biexponential decay function, [47] and the fitting results reveal that the charge recombination lifetime of the flexible Pero-I pero-SCs is longer (6.78 µs) than those of the Pero-Nbased (4.21 µs) and Pero-C-based (3.04 µs) devices. This lifetime observation suggests that the 1D/3D perovskite heterostructure efficiently suppresses the charge recombination processes.…”
Section: Resultsmentioning
confidence: 99%
“…The excessive tBP inside the solid film undergoes slow evaporation and results in pinholes within the HTL. 99,100 The agglomeration and migration of Li x O y are detrimental to the homogeneity of the whole film. [101][102][103] The degradation over time and the de-doping process remain unexplained; hence, the need for a prompt solution arises.…”
Section: Charge Transport Layermentioning
confidence: 99%
“…Perovskite solar cells (PSCs) recently have attracted tremendous research attention and shown great development prospects by demonstrating a certified power conversion efficiency (PCE) of 25.7% which is comparable to that of the state-of-the-art crystalline-silicon solar cells. In spite of such remarkable photovoltaic performance, the instability issues of PSCs remain a critical limiting factor for their commercial application. Therefore, great efforts have been made to engineer the functional layers and their interfaces in the devices for further optimization of performance longevity. …”
Section: Introductionmentioning
confidence: 99%